Automated breast ultrasound compared to hand-held ultrasound in surveillance after breast-conserving surgery. Issue 2 (April 2021) - Depretto, Catherine; Liguori, Alessandro; Primolevo, Alessandra; Di Cosimo, Serena; Cartia, Francesco; Ferranti, Claudio; Scaperrotta, Gianfranco P.
Purpose: To investigate the agreement between automated breast ultrasound (ABUS) and hand-held ultrasound (HHUS) in surveillance of women with a history of breast cancer in terms of recurrences or new ipsilateral or contralateral breast cancer. Methods: The institutional review board approved this retrospective study and informed consent was waived. From April to June 2016, women with dense breasts undergoing annual surveillance with mammography and HHUS after breast-conserving surgery were offered supplemental ABUS (Invenia). HHUS was performed by a breast radiologist and ABUS by a trained technician. Images were reviewed by 2 breast radiologists. A per-patient BI-RADS category was independently assigned in all cases and categories were dichotomized into negative (1, 2, 3) and positive (4, 5). Cohen κ, McNemar, and Wilcoxon statistics were used. Final pathology was used as reference standard for malignant lesions. Results: A total of 154 women (mean age 62±11 years) were enrolled. Time from surgery was a mean of 8±6 years. Cancer prevalence was 4/154 (2.6%). Interreader agreement for ABUS was 1. Intermethod interreader agreement for HHUS and ABUS was substantial for BI-RADS categories (κ = 0.785) and for dichotomic assessment (κ = 0.794). There was no difference in dichotomic assignment between 2 readers ( p = 0.5) but a significant difference in assigning BI-RADS categories ( p < 0.05). Conclusions: A substantial agreement resulted between HHUS and ABUS in surveillance of women with a previous history of breast cancer. In particular, ABUS recognized all cancers detected by HHUS and could play a role in first-level surveillance of women at intermediate risk.